New caribou crisis – then and now - Ruttan, Robert A. (Rangifer, 2012)
The reported decline of the Bathurst herd has caused considerable concern and has raised rumours of a “crisis” in which there is a possibility of extinction. This paper reflects on relevant lessons learned from the officially declared “crisis” of population decline in 1955/56 and a second crisis of overpopulation identified by the author a decade later.